Production of Proteolytic Enzyme from Catfish Waste Using Bacillus subtilis, Proteus vulgaris, and Arthrobacter aurescens (Fountain Journal of Natural and Applied Sciences, 2017)
The world marine captured fishes contribute to more than 50 % of the total world fish production. About 70 % of fish is processed before final sale, resulting in 20-80 %  of  fish  waste  depending  on  the  level  of  processing  and  type  of  fish. The majority of fish wastes are disposed of in the ocean as well as on land. The discards from  the  processing  plants  amount  to  20  million  tonnes,  which  is  equivalent  to  25 %  of  the  world's  total  production  from marine captured fisheries. The fish processing industry generates considerable amounts of by-products such as waste that includes shells, scales, fins and bone frames. Interestingly, they are all often high in protein, which can be processed into useful products. Three organisms Bacillus subtilis, Proteus vulgaris, and Arthrobacter aurescens were isolated and used in the production of the proteolytic enzyme in three different protease production media. B. subtilis, P. vulgaris and A. aurescens were observed to have produced protease best at 48 hr of the second production, 72 hr of the third production, and 72 hr of first production, respectively. Fish waste should not be discarded into the environment, which can cause adverse effect on human health and environmental pollution, but rather they can be used in industries such as food industry in the production of baby foods to help break down the available protein into amino acids required by the body.Keywords: Environmental pollution, Marine habitat, Fish processing, Food protein, Food industry